Catalysis and process of coordination polymerization of ethylene - experiment and theory - Szczegot, K.; Flisak, Z.; Sibelska, I.; Dawidowska-Marynowicz, B. (Polimery, 2022)
Experimental and theoretical studies of coordination polymerization of ethylene have been performed in the presence of precursors - the complexes of Ti, Zr, Hf, V halides with organic Lewis bases, magnesium support [MgCl2(THF)2] and organoaluminium compounds. It was found the correlation between a nature of halide in precursor and vanadium catalyst activity (Table 1, Figs. 1-3). The energetic profiles of insertion (Table 2) and termination [beta-elimination (Fig. 4) or hydrogen transfer (Table 3)] reactions have been computed. Calculated values of insertion barriers as well as of ethylene and active center bond energy correspond well with polymerizations results. Agostic interactions found in the active center, assist in stabilisation of transition metal carbon bond. In the titanium-magnesium catalysts, containing oxygen-donor ligands [tetrahydrofurfurol - Formula (I), its anion - Formula (II) or ethylene glycol dimethyl ether - Formula (III)], the possibility of transformation of O,O’-bidentate ligands into dangling monodentate ones was shown. This may play a crucial role in the catalyst activity. The structures of active centers in catalysts investigated have been proposed (Fig. 7) and has been demonstrated by theoretical way.